Oxygen vacancies on nanosized ceria govern the NOx storage capacity of NSR catalysts. Issue 11 (20th January 2016) - Zhang, Yan; Yu, Yunbo; He, Hong
Abstract : The oxygen vacancies on Pt/BaO/CeO2 govern the NO x storage capacity by creating efficient sites or channels for nitrate formation and its further transformation to Ba-based storage sites. Abstract : Pt/BaO/CeO2 catalysts derived from CeO2 nanomaterials with shapes of rods, cubes, and particles were investigated for NO x storage/reduction. Catalytic tests were performed in a transient flow reactor system. A series of characterization techniques including XRD, TEM, XPS, EXAFS, NO x -TPD, H2 -TPR and in situ DRIFTS were conducted to investigate the electrical, chemical, and structural properties. The NO x storage-reduction performance ranked by the CeO2 support was nanorods > nanoparticles > nanocubes. Amazingly, the CeO2 -nanorod based NSR catalyst possessed a superior NO x storage capacity (NSC) of 913.8 μmol NO x gcat −1 at 350 °C in the absence of H2 O and CO2, which almost reached the theoretical value. Even under harsh lean–rich cycling conditions (90 s vs. 6 s) and a high GHSV of 360 000 h −1, the nanorod-based catalyst also showed the best reduction efficiency, affording 99% NO x conversion levels from 200 °C to 400 °C under the conditions without H2 O and CO2 . The morphology of ceria has significant influences on the selectivity of ammonia, and on the H2 O and CO2 tolerance during the NSR process. For the first time, a close linear correlation was drawn between the NO x storage capacity and the amount of oxygen vacancies of NSR catalysts. Over the NSR catalysts, oxygen vacancies play a crucial role in anchoring Pt. Meanwhile, H2 -TPR results showed that the number of active surface oxygen species trapped in oxygen vacancies was closely related to the NSC value. This suggests that the oxygen vacancies on the NSR surface govern the NO x storage capacity by creating efficient sites or channels for the formation of nitrate and its further transformation to Ba-based storage sites. These findings may be fundamental for designing ceria-based NSR catalysts with better performance.